2015
DOI: 10.1158/1078-0432.ccr-14-0964
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging of Pancreatic Ductal Adenocarcinoma Detects Altered Choline Metabolism

Abstract: Purpose Pancreatic ductal adenocarcinoma (PDAC) is an aggressive and lethal disease that develops relatively symptom-free and is therefore advanced at the time of diagnosis. The absence of early symptoms and effective treatments has created a critical need for identifying and developing new noninvasive biomarkers and therapeutic targets. Experimental Design We investigated the metabolism of a panel of PDAC cell lines in culture and noninvasively in vivo with 1H magnetic resonance spectroscopic imaging (MRSI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 40 publications
8
40
0
Order By: Relevance
“…A recent study has shown high levels of choline and PC in PDAC cell lines and tumors, supporting the importance of CHKa as a potential metabolic target (32). Using bioinformatic analyses and a panel of cell lines, we show that CHKa is overexpressed in PDAC versus nontransformed HPDE pancreatic ductal epithelial cells, as has been reported in lung, breast, colorectal, and bladder cancer cells (11,14), and that PDAC lines rank among those expressing highest CHKa mRNA.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study has shown high levels of choline and PC in PDAC cell lines and tumors, supporting the importance of CHKa as a potential metabolic target (32). Using bioinformatic analyses and a panel of cell lines, we show that CHKa is overexpressed in PDAC versus nontransformed HPDE pancreatic ductal epithelial cells, as has been reported in lung, breast, colorectal, and bladder cancer cells (11,14), and that PDAC lines rank among those expressing highest CHKa mRNA.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we engrafted a piece of tumor tissue onto the ovary to avoid spilling of cancer cells and to maintain the tumor tissue microenvironment. We have used this technique in the past for prostate cancer (24) and for pancreatic cancer (25). In our model, ascites and metastases in the peritoneal cavity, in the liver, on the diaphragm, and in distal lymph nodes are frequent, similar to human disease, since ovarian carcinoma usually metastasizes along the peritoneum throughout the pelvic and abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Human Panc1 (ATCC) and Pa04C cell lines (28, 29) were provided by Dr. Maitra of the Johns Hopkins University School of Medicine in 2012. The Panc1 cell line was established from a primary pancreatic ductal adenocarcinoma from a 56 year old male patient (30), and Pa04C was isolated from a lung metastasis in a 59 year old male patient with stage IV pancreatic adenocarcinoma (28).…”
Section: Methodsmentioning
confidence: 99%
“…Snap frozen muscle samples (40 to 70 mg) were powdered under liquid nitrogen, weighed, and dual phase extraction was performed, as described previously (29). Samples were reconstituted in 500 μl of 1× phosphate buffered D 2 O (90% D 2 O, 10% H 2 O, pH = 7.4), vortexed, centrifuged at 500g for 5 min at 4° C, and supernatants (450 µL) were subjected for 1 H MRS analysis.…”
Section: Methodsmentioning
confidence: 99%